Level and influencing factors of physical activity among 6 - 18 years children and adolescents in Xilingol League, Inner Mongolia Auto-nomous Region - Yanyu WU; Lisi HUANG; Baofeng CHI (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the status and influencing factors of physical activity among children and adolescents aged 6 - 18 years in Inner Mongolia Autonomous Region (Inner Mongolia). MethodsWith cluster sampling, a questionnaire survey on physical activity and its associates was conducted among 4 648 students aged 6 - 18 years in 5 primary and 5 secondary schools in two banner regions of Inner Mongolia during October - November 2020 and April 2021. For the primary school students, the questionnaires were completed by the students' guardians and for secondary school students, the questionnaires were self-administered onsite under the guidance of interviewers. The intensity of physical activity was evaluated by metabolic equivalent (MET). Factors correlated with physical activity were analyzed using binary logistic regression model. ResultsOf the 4 600 students with eligible responses, 1 097 (23.8%) reported having more than 60 minutes of moderate-to-vigorous physical activity (MVPA) per day recommended in the Guidelines on Physical Activity Guide for Chinese Children and Adolescents and 2 987 (64.9%) reported having less than 2 hours of sedentary behavior (SB) per day recommended in the guidelines. Reported by all the eligible students, the average daily time of MVPA was 28.57 minutes and there were significant differences in the average daily MVPA time between the students of different gender (Z = - 6.523, P < 0.001) and among the students with various schooling periods (H = 42.009, P < 0.001); the average daily SB time was 64.28 minutes and there were significant differences in the average daily SB time between the students of different gender (Z = - 2.055, P = 0.040), among the students with various schooling periods (H = 18.151, P < 0.001) and being various ethnic groups (Z = - 4.298, P < 0.001). The results of logistic regression analysis revealed following significant promoting factors for having standard daily MVPA time: paternal education of junior or senior high school, maternal occupation being staff of public institutions and government agencies or employees of agriculture, animal husbandry, forestry and fishery industry, maternal education of senior high school, with divorced parents, with a household monthly income of 5 000 Chinese Yuan and above, suffering from chronic disease, and ever having surgery (P < 0.05 for all); the results also demonstrated multiple promoting factors for having appropriate daily SB time including paternal occupation being staff of public institutions and government agencies or employees of agriculture, animal husbandry, forestry and fishery industry, standard daily/employees of private enterprises, paternal education of college and higher, and maternal occupation being staff of public institutions and government agencies (all P < 0.05). ConclusionDuring 2020 - 2021 among 6 - 18 years old children and adolescents in Xilingol League of Inner Mongolia, the average daily time of MVPA was relatively low according to China' s national guidelines and mainly influenced by gender, schooling period, parents' education, occupation and marital status, household monthly income, whether suffering from chronic disease, and the history of surgery; but the average daily SB time was at an appropriate level and impacted mainly by paternal occupation, maternal education, household monthly income, and the history of surgery.